The Effect of Commercial Marketing on Customer Satisfaction: A Field Study Applied to Some Commercial Organizations in Cairo - Saleh, Sahar Mohamed Anwar (The Arab Journal of Administration, 2024)
The problem of the current study was to find out the impact of commercial marketing on customer satisfaction, a field study applied to some commercial organizations in Cairo governorate. The study used the descriptive analytical approach in answering the study questions and in testing the study hypothesis. The data was collected by a Polling list distributed to a stratified non-random sample of some clients from 5 commercial organizations in Cairo Governorate. The sample size was 60. The SPSS program was used to tabulate the results of the study. Among the most important results of the study: There was a positive and direct effect of commercial marketing on clients satisfaction in some telecommunications companies. The extent of the impact of each commercial marketing dimension (service, price, information, promotion, distribution, privacy) on clients satisfaction in some telecommunication companies is high. Acceptance of the main hypothesis of the study, that there was a statistically significant direct relationship at a significant level (a = 0.05) between commercial marketing and achieving clients satisfaction in some telecommunications companies in Cairo Governorate. Among the most important recommendations of the study: The need to quickly deal with clients complaints and respond to them. The need to increase the speed of the Internet and strengthen the network. Increasing interest in clients satisfaction with the services provided by telecommunication companies. Ensuring transparency and credibility in the information provided to customers by telecommunications companies.